Carbonation potential of concrete debris fines and its valorisation through mineral carbonation. (6th December 2021) - Nedunuri, Aparna Sai Surya Sree; Mohammed, Asfand yar; Muhammad, Salman
Graphical abstract: Highlights: Concrete debris fines obtained from CDW found to have carbonation potential. CDF were valorized as laboratory scale masonry blocks of strength 6–13 MPa. TGA, XRD and SEM analysis confirms the formation of polymorphs of calcium carbonate. Concrete debris fines can sink around 40–85 g of CO2 per kilogram. Abstract: In this study, the concrete debris fines obtained from demolished concrete structures of different ages were analysed for its carbonation potential. The CO2 uptake of the concrete during the service life (of up to 60 years) suggested that it still has a lot of potential for further carbonation. The carbonation potential of the concrete debris fines was analysed by measuring the amount of carbonates after subjecting to accelerated carbonation through the slurry carbonation using sonication. An attempt was made to valorise them as masonry blocks through mineral carbonation. Laboratory-scale monoliths that represent the masonry blocks were prepared by compacting the concrete debris fines in the form of a cube, which were then carbonated in a carbonation chamber at elevated pressure. The carbonated monoliths were analysed for CO2 uptake (%), compressive strength, porosity, morphology and mineral phases. The strength achieved have met the strength requirement of masonry blocks. Calcite, vaterite and aragonite phases were observed to have formed during carbonation which was confirmed by thermal analysis, scanning electron images and quantitative phase analysis.